Liver Fibrosis Progression despite HCV Cure with Antiviral Therapy in HIV–HCV-Coinfected Patients. Issue 3 (April 2015) - Labarga, Pablo; Fernandez-Montero, Jose V; De Mendoza, Carmen; Barreiro, Pablo; Pinilla, Javier; Soriano, Vincent
Background: Accelerated liver fibrosis and more frequent hepatic decompensation events and liver-related deaths are characteristically seen in chronic hepatitis C patients coinfected with HIV compared with HCV-monoinfected individuals. Quantitative estimates of long-term clinical benefits derived from curing HCV with antiviral therapy in coinfected patients are scarce, despite being needed for accurate cost-effectiveness decisions using expensive direct-acting antivirals in this population. Methods: We retrospectively examined all HIV–HCV-coinfected patients followed at one reference clinic in Madrid since 2004. Liver fibrosis was measured longitudinally using elastometry; changes above 30% in kilo-pascal units were considered as significant. Results: A total of 568 HIV–HCV-coinfected patients were examined. Pegylated interferon/ribavirin therapy had been given to 396 (69.7%) of whom 138 (34.8%) had achieved sustained virological response (SVR). Mean follow-up was of 6.8 (±1.5) years for hepatic events and 4.4 (±0.8) years for liver fibrosis. Hepatic decompensation events, liver-related deaths and significant liver fibrosis progression occurred less frequently in SVR than in non-treated/treatment failures. Although regression of liver fibrosis occurred in most SVR patients, fibrosis significantly progressed in 7.2% of them, in association with higher plasma HIV RNA ( P =0.005) and longer exposure to HIV protease inhibitors ( P =0.009). Conclusions: Achievement of SVR dramatically reduces the risk of hepatic decompensation events and liver-related deaths in HIV–HCV-coinfected patients. Although liver fibrosis generally improves following HCV cure, worsening may occur in association with uncontrolled HIV replication and prolonged exposure to protease inhibitors. Thus, periodic assessment of liver fibrosis is warranted after SVR and screening for liver cancer should continue in coinfected patients with advanced liver fibrosis.